2014
DOI: 10.1111/jpy.12188
|View full text |Cite
|
Sign up to set email alerts
|

Menadione‐induced caspase‐dependent programmed cell death in the green chlorophyte Chlamydomonas reinhardtii

Abstract: Menadione, a quinone that undergoes redox cycles leading to the formation of superoxide radicals, induces programmed cell death (PCD) in animals and plants. In this study, we investigated whether the unicellular green alga Chlamydomonas reinhardtii P.A.Dangeard is capable of executing PCD upon exposure to menadione stress. We report here, the morphological, molecular, and biochemical changes after menadione exposure of C. reinhardtii cells. The effect of menadione on cell death has been shown to be dose-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 110 publications
1
10
0
Order By: Relevance
“…Cells were grown and maintained by periodic transfers in Tris Acetate Phosphate (TAP; pH 7) as mentioned by Sirisha et al . 62 .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown and maintained by periodic transfers in Tris Acetate Phosphate (TAP; pH 7) as mentioned by Sirisha et al . 62 .…”
Section: Methodsmentioning
confidence: 99%
“…Menadione multiorgan toxicity is associated with overwhelmed antioxidant defense resulting from overproduction of •O 2 − and H 2 O 2 . Interestingly, studies have reported a nexus between oxidative stress and testicular toxicity .…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of Fe 2+ , H 2 O 2 produced is converted to •OH via Fenton reaction . All these culminate to oxidative stress associated with menadione toxicity and is further aggravated by glutathione depletion . Furthermore, apoptosis, mitochondrial dysfunction, and DNA fragmentation are also associated with menadione toxicity …”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, several authors have reported evidence for the occurence of apoptosis in the unicellular green alga C. reinhardtii (Moharikar et al 2006;Sirisha et al 2014;Yordanova et al 2010Yordanova et al , 2013Zuo et al 2012).…”
Section: Discussionmentioning
confidence: 99%